The Applicability of Fama-French Three-factor Model to Beijing Stock Market - Zhang, Hanqi (International Journal of Global Economics and Management, 2024)
This paper takes Beijing A-shares as a research focus, divides them into four groups by market value and book-to-market ratio, and uses Fama-French three-factor model to conduct relevant empirical test and regression analysis. The experimental results show that the three factors of the three-factor model have good predictability of the rate of return of Beijing Stock Exchange portfolio, and the volatility of the return rate is the most significant sensitivity to market fluctuations. The ratio of market capitalization and book value has a low explanatory power for the impact of stock risk-return fluctuation.